2012
DOI: 10.1007/s10616-012-9440-7
|View full text |Cite
|
Sign up to set email alerts
|

Ischemic cardiac tissue conditioned media induced differentiation of human mesenchymal stem cells into early stage cardiomyocytes

Abstract: Mesenchymal stem cells (MSCs) are multipotent, can be easily expanded in culture and hence are an attractive therapeutic tool for cardiac repair. MSCs have tremendous potential to transdifferentiate to cardiac lineage both in vitro and in vivo. The present study examined the differentiation capacity of conditioned media derived from ischemic cardiac tissue on human MSCs. Human Bone marrow-derived MSCs after due characterization by immunocytochemistry and flow cytometry for MSC specific markers were induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Concomitantly, it was found that hepatic-associated markers of HP14.5 cells treated with 5-azaC alone, did not increase significantly, suggesting that DNA hypomethylation is not the only factor that determines gene expression during the hepatic cell differentiation process; the appropriate induced culture conditions and the microenvironment also have an effect on transcriptional control. Similarly, MSCs may be induced to differentiate into cardiomyocytes by 5-azaC, although it is difficult to to obtain functional beating myocardial cells (51). DLK and AFP proteins are markers of hepatic stem cells (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Concomitantly, it was found that hepatic-associated markers of HP14.5 cells treated with 5-azaC alone, did not increase significantly, suggesting that DNA hypomethylation is not the only factor that determines gene expression during the hepatic cell differentiation process; the appropriate induced culture conditions and the microenvironment also have an effect on transcriptional control. Similarly, MSCs may be induced to differentiate into cardiomyocytes by 5-azaC, although it is difficult to to obtain functional beating myocardial cells (51). DLK and AFP proteins are markers of hepatic stem cells (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…MSCs induced with ischaemic cardiac conditioned media showed positive reaction for GATA-4 , Nkx 2.5 and MLC-2a , suggesting cardiomyogenic differentiation of MSCs, as compared with the negligible effect by a non-ischaemic environment exerted on the MSCs [ 247 ]. Cardiomyogenic media-primed MSCs enhanced expressions of sarcomeric α-actinin and Cx-43 , establishing themselves as better therapeutic agents than direct MSC transplantation [ 248 ].…”
Section: Main Textmentioning
confidence: 99%
“…Thus, this study demonstrated the function of cardiomyocyte LOX-1 in immune responses. In the conditioned media derived from ischemic human cardiac tissue, which induced differentiation of human mesenchymal stem cells into early stage cardiomyocytes, C-type lectin superfamily member 13 (Clecsf13) was identified by a proteomics analysis as one of the three differentially expressed proteins (Ramesh et al, 2012). Although the exact role of Clecsf13 in cardiac regeneration needs further analysis, its differential expression in ischemic media at least suggests a role of Clecsf13 in myocardial ischemia.…”
Section: Prrs In Cardiomyocytesmentioning
confidence: 99%